Fire-vegetation interplay in a mosaic structure of Quercus suber woodlands and Mediterranean maquis under recurrent fires (Forest Ecology and Management, 2011)
We examined the effects of ﬁre recurrence on a mosaic structure of Quercus suber and Erica-Cistus shrubland communities of Southeastern France in order to improve the understanding of ﬁre-vegetation interplay. Plant communities that were similar in 1959 (woodlands on shrublands called maquis on acidic soils) were compared along a gradient of ﬁre recurrence, from 0 to 4 ﬁres, with different time intervals between ﬁres. The results showed that understory cover increased roughly with ﬁre recurrence, whereas tree height, cover, density, stand basal area and litter depth decreased. Different ﬁre recurrences along the past decades led to different vegetation types. High ﬁre recurrence corresponded to maquis and sparse cork-oak woodlands while pure oak woodlands established in the absence of ﬁre during the same period. In all, the diversity of tree diameter decreased with ﬁre recurrence. High ﬁre recurrence (3 or 4 ﬁres in 50 years) led to a simple vertical structure of vegetation with a mono-layered shrub cover and few Quercus suber trees. In contrast, spatial connections between plants were maximal at longer time intervals, leading to a multi-layered vegetation. We ﬁnally discuss the potential implications of past ﬁres on the behavior of future ﬁres in the perspective of a sustainable management of these Mediterranean ecosystems.